Hierarchical spheres of Mg–Al LDH for the removal of phosphate ions: effect of alumina polymorph as precursor. Issue 47 (28th October 2019) - Sudare, Tomohito; Zenzai, Atsushi; Tamura, Shuhei; Kiyama, Masahiro; Hayashi, Fumitaka; Teshima, Katsuya
Abstract : In order to tailor the morphology of the layered double hydroxide (LDHs) particles, we focused on a synthesis method involving the use of Al2 O3 as a precursor, employing Al2 O3 with different crystal structures ( e.g., α-Al2 O3, θ-Al2 O3, and γ-Al2 O3 ) as well as amorphous Al2 O3 . Abstract : In order to tailor the morphology of the layered double hydroxide (LDHs) particles, we focused on a synthesis method that involves the use of Al2 O3 as a precursor, employing Al2 O3 with different crystal structures ( e.g., α-Al2 O3, θ-Al2 O3, and γ-Al2 O3 ) as well as amorphous Al2 O3 . A three-dimensional network of plate-shaped LDH particles was formed when θ-Al2 O3 and γ-Al2 O3 were used, even though α-Al2 O3 barely reacts to form the LDH phase. Finally, adsorption tests involving HPO4 2− ions confirmed that the fabricated LDH particles exhibited high ion-removal rates. The LDH particles prepared with θ-Al2 O3 and γ-Al2 O3 could remove the hydrogen phosphate ions (HPO4 2− ) in a concentration of 0.40 mmol g −1 completely within 10 min; this is approximately 20 times shorter than the time taken by the LDH particles prepared from amorphous Al2 O3 .